Recombinant Ricin Toxin Binding Subunit B (RTB) Stimulates Production of TNF-α by Mouse Macrophages Through Activation of TLR4 Signaling Pathway - Xu, Na; Yu, Kaikai; Yu, Haotian; Zhang, Jianxu; Yang, Yang; Dong, Mingxin; Wang, Yan; Chang, Ying; Sun, Yucheng; Hou, Yanguang; Sun, Chengbiao; Wan, Jiayu; et al. (Frontiers in Pharmacology, 2020)
Ricin toxin binding subunit B (RTB) is a galactose-binding lectin protein derived from the beans of the castor oil plant (Ricinus communis). Our previous studies have reported a direct immunomodulatory effect of recombinant RTB, which stimulates RAW264.7 cells to produce cytokines including TNF-α. However, the role of RTB in innate immune response and its specific mechanism have not been reported in detail. In this work, the results showed that RTB treatment of macrophages significantly increased TLR4 protein levels. RTB also activated TLR4 downstream events, including MyD88, IRAK, and TRAF6, resulting in macrophage activation and TNF-α production. This process is reflected in the increase of IκB phosphorylation. TLR4 knockdown macrophages treated with RTB exhibited greatly reduced IκB phosphorylation and TNF-α secretion. Moreover, treatment with MyD88 inhibitor also suppressed TNF-α production. The docking of RT and TLR4 was simulated by computer, and the contact residues were concentrated on RTB. Our results suggest that recombinant RTB can activate mouse macrophages to secrete TNF-α through activation of NF-κB via the TLR4 signaling pathways.